ENHANCING ACADEMIC ACHIEVEMENT THROUGH THE APPLICATION OF THE 5E LEARNING CYCLE MODEL - Lasaiba, Mohammad Amin; Lasaiba, Djamila (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
This study aims to evaluate the effectiveness of the 5E learning cycle model in improving student learning outcomes and their engagement in the learning process. The research adopts the Classroom Action Research method, conducted at SMA Muhammadiyah Ambon, with a sample from Class XI through random sampling. Data collection includes observation, tests, and documentation. Research instruments comprise observation sheets guiding the investigation, tests assessing students' mastery level, and documentation gathering relevant materials about the research context. Data analysis involves both qualitative and quantitative methods. Quantitative analysis processes numerical data, while qualitative analysis involves reduction, display, and verification. The research findings highlight the effectiveness of the 5E learning cycle model in enhancing student learning outcomes and engagement. Throughout the cycles, there is a noticeable increase in learning completeness based on cognitive assessments. There was a significant increase of 72.5% in Cycle I, and this trend further substantially increased in Cycle II by 85.0%. Performance assessments also reflected these positive trends, showing a 75.0% increase in the first Cycle and a significant 87.5% improvement in the second. This study, marked by its effectiveness, successfully concluded at the end of Cycle II. This success is evident in applying the learning model, the learning process involving teacher and student activities, and the overall improvement in student learning outcomes across cognitive components. The 5E learning cycle model holds significance in Education, emphasizing student-student-centred Learning. Therefore, it is recommended that the 5E learning cycle model be implemented sustainably in educational activities to create a dynamic learning environment and enhance overall learning outcomes.